Cover crops and herbicide timing management on soybean yield under no‑tillage system - Nascente, Adriano Stephan; Crusciol, Carlos Alexandre Costa (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of cover crops and timing of pre‑emergence herbicide applications on soybean yield under no‑tillage system. The experiment consisted of four cover crops (Panicum maximum, Urochloa ruziziensis, U. brizantha, and pearl millet) and fallow, in addition to four herbicide timings (30, 20, 10, and 0 days before soybean sowing), under no‑tillage system (NTS), and of two control treatments under conventional tillage system (CTS). The experimental design was a completely randomized block, in a split‑plot arrangement, with three replicates. Soybean under fallow, P. maximum, U. ruziziensis, U. brizantha, and pearl millet in the NTS and soybean under U. brizantha in the CTS did not differ significantly regarding yield. Soybean under fallow in the CTS significantly reduced yield when compared to the other treatments. The amount of straw on soil surface did not significantly affect soybean yield. Chemical management of P. maximum and U. brizantha near the soybean sowing date causes significant damage in soybean yield. However, herbicide timing in fallow, U. ruziziensis, and pearl millet does not affect soybean yield.